Kinetic studies and adsorptive removal of chromium Cr(VI) from contaminated water using green adsorbent prepared from agricultural waste, rice straw - Islam, Izaz Ul; Ahmad, Mushtaq; Ahmad, Maqbool; Rukh, Shah; Ullah, Ihsan (European Journal of Chemistry, 2022)
Water pollution caused by heavy metals is of great concern because of rapid industrialization, lack of wastewater treatment, and inefficient removal of these metals from wastewater. The present project was designed to develop a green adsorbent from rice straw and to investigate it for the removal of chromium from chromium-contaminated water. Rice straw biochar was prepared and then modified with FeCl3·6H2O and FeSO4·7H2O to enhance its Cr removal efficiency. Modified and unmodified biochar were characterized by Scanning Electron Microscope (SEM), Energy Dispersive X-ray Spectroscopy (EDS), and Fourier Transform Infrared Spectroscopy (FTIR). Batch sorption experimentations were performed to inquire about adsorption kinetics, isotherms, and Cr(VI) adsorption mechanism onto iron-modified rice straw biochar (FMRSB). The results specified that the apex adsorption capability of the adsorbent for chromium was 59 mg/g and the maximum removal efficacy was 90.9%. Three isotherm models, Sips, Freundlich, and Langmuir models were applied to the experimental data. Among them, the Sips isotherm model reveals the most excellent fitting with a maximum correlation coefficient (R2 = 0.996) that was adjusted to the experimental data. Regarding kinetic studies, the Pseudo second-order (PSO) exhibits the best fitting with a higher correlation coefficient (R2 = 0.996). The kinetic equilibrium data expressed that the adsorption of Cr(VI) on the FMRSB surface was chemisorption. The mechanism of adsorption of Cr(VI) on FMRSB was predominantly regulated by anionic adsorption through adsorption coupled reduction and electrostatic attraction. The present study demonstrated that the use of modified biochar prepared from agricultural wastes is an environmentally safe and cost-effective technique for the removal of toxic metals from polluted water.